Influence of acetic and butyric acid and gas release modes on immobilized Clostridium acetobutylicum (DSMZ 792) in repeated batch experiments. Issue 5 (28th May 2022) - Stein, Ullrich Heinz; Abbasi-Hosseini, M.; Bochmann, G.; Fuchs, W.
Abstract: The effects of supplementation of standard media with metabolic intermediates (2 g/L butyric acid, 2 g/L butyric acid + 1.5 g/L acetic acid) on butanol and hydrogen production/yield were evaluated. Fermentations were conducted with immobilized Clostridium acetobutylicum (DSMZ 792). Additionally, the influence of gas release modes (constant gas release vs. interval gas release) was tested in all setups to evaluate butanol and hydrogen production and yields. Fermentations were implemented in repeated batch mode (48 h, 37 °C, 100 rpm). Overpressure conditions had a negative impact on volumetric hydrogen production and hydrogen yield and a positive impact on butanol yield. Supplementation significantly increased the butanol concentrations in constant gas release mode, by 23.6%. When interval gas mode was applied in the supplemented fermentations, the butanol concentrations decreased by 8.4% when butyric acid was fed, and reached similar concentrations when both acids were added. The highest butanol concentration and volumetric butanol production rate of 9.6 ± 0.6 g/L and 0.2 ± 0.0 g/L*h, respectively, were reached with butyric acid supplementation and constant gas release mode. The highest volumetric hydrogen production was reached with the constant gas release mode in fermentations conducted with the addition of both acids, and reached 165 ± 9 mL/L*h. Graphical Abstract: Abstract : UF0001 Highlights: Interval gas release mode increased the butanol yield and decreased the hydrogen yield Supplementation of acids increased volumetric butanol production rate